Description and biological observations on a new species of deepwater symphurine tonguefish (Pleuronectiformes: Cynoglossidae: Symphurus) collected at Volcano–19, Tonga Arc, West Pacific Ocean - Munroe, Thomas A.; Tyler, Jennifer; Tunnicliffe, Verena (Zootaxa, 2011)
Symphurus maculopinnis n. sp., described on a single specimen (USNM 398820; 84.4 mm SL), was collected by a remotely operated vehicle (ROV) exploring a hydrothermal vent area located at 561 m on Volcano–19, Tonga Arc, West Pacific (24°48.439’ S, 177°0.009’ W). This new species is distinctive and readily diagnosed from congeners by the following combination of characters: 1–2–2–2–1 pattern of interdigitation of dorsal proximal pterygiophores and neural spines (ID pattern), 14 caudal-fin rays, 3+6 abdominal vertebrae, 49 total vertebrae, 89 scales in a longitudinal row, 92 dorsal-fin rays, 77 anal-fin rays, blunt squarish snout, thick blind-side lips with conspicuous plicae, and conspicuous ocellated (sometimes partially) spots on posterior dorsal and anal fins. Among Symphurus, only S. ocellatus von Bonde, collected at deepwater locations off East Africa, features a similar ID pattern, 14 caudal-fin rays and spots on the posterior dorsal and anal fins. Symphurus maculopinnis differs distinctly from S. ocellatus in its lower and non-overlapping meristic features (49 vs. 54–56 total vertebrae; 92 vs. 97–103 dorsal-fin rays; and 77 vs. 85–89 anal-fin rays), its squarish (vs. pointed) snout, and thick, plicated blind-side lower lip (vs. thin, non-plicated blind-side lower lip). Additional specimens (N= 56) of S. maculopinnis observed and filmed in situ near active venting sites located between ca. 433-561 m on Volcano–19 provide the basis for behavioral and ecological information recorded for the species. Videotapes reveal one individual of S. maculopinnis featuring reversed (dextral) asymmetry from that typical (sinistral) for members of the Cynoglossidae. Specimens with reversed asymmetry are relatively rare in this family and this S. maculopinnis represents only the second known reversed individual among the approximately 42 species of deep-sea (>200 m) Symphurus.